LEADERSHIP CREATIVE VILLAGE - Manap, Abdul; I Nyoman Tri Sutaguna; Mutmainah Mutmainah; Atik Sekianti; Yusnindar Yusnindar (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
The innovative leadership of the Chief District Officer of Cianjur District in the implementation of the Village Innovation was seen and measured to the extent to which the commitment and political will of the Head of the District in providing public services and providing public goods to its citizens. In addition, the Innovative Leadership Capacity of the Head of the District will be reviewed from the perspective of the innovative development visions built, the strategic steps taken to drive innovation, and the stability of his leadership. The research focuses on the leadership of regional heads in the implementation of smart innovation camp with a theoretical approach to leadership and innovation. This research uses a qualitative approach (qualitative approach). Data sources include people, events, places and documents. Data collection techniques include in-depth interviews, documentation and observations. Data analysis techniques are interactive models. (interactive model analysis). The results of the research show that Creative Village Innovation is a technology-based program that focuses on the village community as well as the implementation center in the village office. The program designs the village to have an integrated programme framework that blends the use of fiber-optic information and communication technology (ICT), productive economic activities, creative economic activity, improved education, health, and poverty alleviation efforts.